ANALISIS UNSUR INTRINSIK CERPEN â€œPENGEMIS DAN SHALAWAT BADARâ€ KARYA AHMAD TOHARI - Ujang Andri Ujang (IKIP Siliwangi, 2021)
Short stories are part of fictional literary works based on the results of essays and human thoughts in telling a problem that is told through the characters briefly starting from the introduction, the problems to the end of the problems experienced by the characters. In general, short stories literary works tell a variety of frenzied problems of life. A short story has a constructing element, namely the intrinsic element. Intrinsic elements include theme, character, setting, characterization, style, point of view, language style and message. In this case, the researcher will analyze the intrinsic elements of Ahmad Tohari's short story entitled